2020
DOI: 10.3390/jmse8090668
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Operational Modeling in Support of Oil Spill Response

Abstract: Following the 2010 Deepwater Horizon accident of a massive blow-out in the Gulf of Mexico, scientists from government, industry, and academia collaborated to advance oil spill modeling and share best practices in model algorithms, parameterizations, and application protocols. This synergy was greatly enhanced by research funded under the Gulf of Mexico Research Initiative (GoMRI), a 10-year enterprise that allowed unprecedented collection of observations and data products, novel experiments, and international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 234 publications
(294 reference statements)
1
26
0
Order By: Relevance
“…The paper is structured as follows: in Section 2, the physical transport and the physico-chemical OWPs are described; in Section 3, the state-of-the-art oil spill models are critically reviewed; Section 4 presents a critical comparison of existing oil spill models, while Section 5 proposes technical recommendations and modeling improvements. The present work expands and updates similar critical review papers, such as [10][11][12][13][14][15].…”
Section: Periodsupporting
confidence: 66%
See 2 more Smart Citations
“…The paper is structured as follows: in Section 2, the physical transport and the physico-chemical OWPs are described; in Section 3, the state-of-the-art oil spill models are critically reviewed; Section 4 presents a critical comparison of existing oil spill models, while Section 5 proposes technical recommendations and modeling improvements. The present work expands and updates similar critical review papers, such as [10][11][12][13][14][15].…”
Section: Periodsupporting
confidence: 66%
“…This process has a significant role in the vertical interchange among the surface oil spill and the vertical layers of the water column [112]. The main source of uncertainty in oil spill simulations arises from uncertainties in the forcing of models, i.e., ocean circulation, wave and atmospheric coupled models, therefore reliable forecasts are essential for accurately determining the advective transport [15,136]. The volume of turbulent mixing is widely represented via an eddy diffusivity coefficient.…”
Section: Turbulent Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…that may affect large-scale circulation is crucial for improving preparedness and response measures in the case of large oil pollution incidents. In a synthesis study that discusses the scientific experience gained in the aftermath of the DwH oil spill, Barker et al [52] argued that high-resolution modeling is necessary to resolve coastal and shelf processes. We showed that among other major meteorological and oceanographic conditions that mainly control the LC/FC evolution, specific southeastern GoM mesoscale processes may also participate in the evolution of hydrocarbon pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The AMSM project assessed the state of the art of oil spill models used by the private sector, the U.S. and Canadian governments, and other international agencies. In addition to the GNOME model used by the U.S. government, some of these models include the Canadian Oil Spill Modelling Suite, Marine Environmental Modeling Workbench, and OILMAP and SIMAP [23][24][25]. The project identified ice-related gaps in existing oil spill models (e.g., under ice oil storage capacity and spreading, melting, and pooling of oil on ice) that might address them.…”
Section: Introductionmentioning
confidence: 99%